2021
DOI: 10.3390/v13101956
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Countrywide Epidemic Spread of Influenza A(H1N1)pdm09 Virus in Kenya between 2009 and 2018

Abstract: The spatiotemporal patterns of spread of influenza A(H1N1)pdm09 viruses on a countrywide scale are unclear in many tropical/subtropical regions mainly because spatiotemporally representative sequence data are lacking. We isolated, sequenced, and analyzed 383 A(H1N1)pdm09 viral genomes from hospitalized patients between 2009 and 2018 from seven locations across Kenya. Using these genomes and contemporaneously sampled global sequences, we characterized the spread of the virus in Kenya over several seasons using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The genetic diversity of A(H1N1)pdm09 viruses in specific regions arising from multiple virus introductions and subsequent establishment of local transmission clusters [13] composed of viruses harboring considerable amino acid substitutions in antigenic epitopes and RBS could lead to predominance of circulating viruses that are not closely matched to previously selected vaccine strains as shown in our study. In countries like Kenya, where influenza virus spread is year-round [9], there also exists unpredictability of which genetic virus strain may predominate and when.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…The genetic diversity of A(H1N1)pdm09 viruses in specific regions arising from multiple virus introductions and subsequent establishment of local transmission clusters [13] composed of viruses harboring considerable amino acid substitutions in antigenic epitopes and RBS could lead to predominance of circulating viruses that are not closely matched to previously selected vaccine strains as shown in our study. In countries like Kenya, where influenza virus spread is year-round [9], there also exists unpredictability of which genetic virus strain may predominate and when.…”
Section: Discussionmentioning
confidence: 90%
“…Analysis of virus sequence data from Kenya during the pandemic in 2009 identified the introduction of clades 2 and 7 viruses into Kenya [21]. We recently confirmed these findings and showed that clades 6 and 7 viruses were introduced into Kenya, disseminated countrywide, and persisted across multiple epidemics as local transmission clusters [13]. A recent study from Kenya reported the circulation of clade 6B, subclade 6B.1, and subclade 6B.2 viruses in the 2015-18 influenza seasons [22].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations